2018
DOI: 10.1021/acs.est.8b06201
|View full text |Cite
|
Sign up to set email alerts
|

Validation and Application of a 3-Step Sequential Extraction Method to Investigate the Fraction Transformation of Organic Pollutants in Aging Soils: A Case Study of Dechlorane Plus

Abstract: A 3-step sequential extraction method was developed to characterize the “labile,” “stable-adsorbed,” and “bound-residue” fractions of Dechlorane Plus (DP) in aging soils. Afterward, the proposed method was used to observe the transformation of DP fractions during aging. Slight decrease of total DP concentrations suggested there was a rather limited degradation, with only 4.2–8.2% of initial DP having degraded after 260 days. The labile fraction, which indicated the bioavailability of DP, decreased from 25.5% t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 59 publications
0
8
1
Order By: Relevance
“…This finding differs from previous outputs of black carbon (BC) and heavy metal in the BS revealing the absolutely dominant role of sedimentation (Fang et al, 2015;Liang et al, 2018). DP were relative persistence in the environment (Cheng et al, 2019;Huang et al, 2020). However, previous study had also found dechlorination (DP [-Cl þ H] and ] degradation products) and other unidentified DP-degradation products by photodegradation (Canada, 2019).…”
Section: Fractional Abundances Of Dp Isomerscontrasting
confidence: 57%
“…This finding differs from previous outputs of black carbon (BC) and heavy metal in the BS revealing the absolutely dominant role of sedimentation (Fang et al, 2015;Liang et al, 2018). DP were relative persistence in the environment (Cheng et al, 2019;Huang et al, 2020). However, previous study had also found dechlorination (DP [-Cl þ H] and ] degradation products) and other unidentified DP-degradation products by photodegradation (Canada, 2019).…”
Section: Fractional Abundances Of Dp Isomerscontrasting
confidence: 57%
“…However, the hydrophobicity of DP (log K ow = 9.0) hindered mobility to the extent that it contributed very little to dissipation. Owing to these effects, the half-life of DP was greatly shortened to 105 days in the root compartment for the S1 soil, while this value was 1325 in the unplanted soil estimated by our previous study …”
Section: Resultsmentioning
confidence: 71%
“…This procedure was repeated three times, and the combined extracts were filtered through a 0.22 μm PTFE syringe filter and concentrated to 1 mL for instrumental analysis. The fractions of DP in soil were determined using a 3-step sequential extraction method described in our previous study . Analysis of DP was performed with GC–MS (a Thermo DSQ II system) operating in the electron capture negative ionization (ECNI) mode.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations